(untitled) (Universal International Scientific Journal, 2026)
This scientific article presents theoretical and practical recommendations on the long term concept of training highly qualified gymnasts, based on the unity of organizational and program methodological foundations, material and technical support of the training process, systematic and integrated use of special means and methods, as well as pedagogical and medical-biological control